2021
DOI: 10.1007/s00426-021-01583-6
|View full text |Cite
|
Sign up to set email alerts
|

What matters in making demand-based decisions: Time alone or difficulty too?

Abstract: Which task is easier, doing arithmetic problems of specified form for some specified duration, or carrying a bucket of specified weight over some specified distance? If it is possible to choose between the “more cognitive” task and the “more physical” task, how are the difficulty levels of the tasks compared? We conducted two experiments in which participants chose the easier of two tasks, one that involved solving addition or multiplication problems (Experiment 1) or addition problems with different numbers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…As predicted, participants switched tasks more often in blocks where task switches were associated with (relatively) lower temporal costs. This finding is consistent with previous studies showing that the duration of a given action represents a cost factor in decision making (Janczyk et al, 2022;Potts et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…As predicted, participants switched tasks more often in blocks where task switches were associated with (relatively) lower temporal costs. This finding is consistent with previous studies showing that the duration of a given action represents a cost factor in decision making (Janczyk et al, 2022;Potts et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…The underlying idea is that human prob-Switching Cognitive Mechanisms lem solvers might be especially willing to avoid cognitive effort (Kool et al, 2010). However, it has been shown that for voluntary task switches, physical costs factor in as well (Janczyk et al, 2022;Potts et al, 2018). Physical switch costs are present to some degree in the present paradigm (manual rotation necessitates pressing a key that needs preparation) but are likely more pronounced in more physically engaging situations like, for example, when walking to a computer to gain access to a CM (compare Storm et al, 2017).…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…Other task structures might place the weight on attentional or other demands for task optimization. Furthermore, the subjective feeling of effort, as distinct from effort avoidance, may likewise derive from multiple task features ranging from task performance to cognitive or physical task difficulty and may depend on situational factors (Janczyk et al, 2022). Future studies should verify the contribution of multiple factors on effort costs and directly test the effect of task context and structure on the determinants of effort avoidance.…”
Section: Discussionmentioning
confidence: 99%